Conventional vs virtual notice board: The effectiveness of information delivery in higher education institution / Roslilee Ab.Halim … [et al.] - Ab.Halim, Roslilee; Abd Jabar, Faizan; Mohamad, Siti Aishah; Azer, Ilyani; Ab.Halim, Norliwa (2011)
The conventional or traditional notice board is widely used in most universities all over the world as a tool to make announcement or deliver latest information to students. However, as the information technology (IT) is growing at incredible pace, it has definitely transformed the way we live, communicate, learn and do business. As the young generation embraced technology and became attached to it, universities or higher education institutions had to keep up with the transformation in order to smoothen daily activities. Therefore, the aim of this paper is to investigate the effectiveness of information delivery in higher education institution. Do these young IT savvy students go and read announcement or information from the notice board or do they opt to read them from the virtual notice board? Does the announcement or information updates on the notice board reach the students or do we have to develop a friendlier virtual notice board that could be accessed from anywhere? The population of this study consists of students from Universiti Teknologi MARA Cawangan Pahang. Six diploma programmes were randomly chosen and a total of356 questionnaires were distributed. The selection of sample was based on stratified random sampling technique. The SPSS Version 18.0 was used to conduct data analysis. Data was analyzed for descriptive statistics such as mean, frequency and percentage